Sunbed use legislation in Europe: assessment of current status. (27th February 2019) - Longo, M.I.; Bulliard, J.L.; Correia, O.; Maier, H.; Magnússon, S.M.; Konno, P.; Goad, N.; Duarte, A.F.; Oláh, J.; Nilsen, L.T.N.; Peris, K.; Karls, R.; et al.
Abstract: Background: The use of UV‐emitting tanning devices for cosmetic purposes is associated with an increased risk of melanoma and non‐melanoma skin cancer. Young women are the most frequent users, therefore, there is an increasing concern about the regulation of sunbed use. Objective: The primary objective is to assess the current legislation on sunbed use among European countries. Methods: We developed a 30‐item questionnaire to gather the most relevant information about sunbed use legislation. The questionnaire was sent to Euromelanoma coordinators and to designated coordinators out of the Euromelanoma network. Results: We obtained a response rate of 64%. More than 25% of the countries did not report any specific legislation. Roughly one‐third of the countries does not have a restriction for minors. Even in countries with a specific legislation, a lack or insufficient enforcement of age limit was observed in up to 100% of the inspections based on the PROSAFE report from 2012. Self‐tanning devices were reported in 50%, and almost 40% of countries do not require supervision of use. Although a warning display is required in 77% of cases, a signed informed consent is not required in 80%. In the vast majority of cases, the number of licensed or closed tanning centres is unknown. Conclusions: Despite the evidence of its harmful effects, and its frequent use by young people, many of whom are at high risk of skin cancer because of fair skin, a significant number of European countries lack a specific legislation on tanning devices. In order to limit the access of young people to sunbeds, a more strictly enforced regulation is needed, as well as regulation regarding advertisement, and location of tanning centres, in addition to health promotion campaigns that target the vulnerable population of young women seeking its use for improved cosmesis.